Cervical cytological abnormalities and human papilloma virus infection in women infected with HIV in Southern India. Issue 12 (19th September 2016) - Thunga, Suchitra; Andrews, Anusmitha; Ramapuram, John; Satyamoorthy, Kapaettu; Kini, Hema; Unnikrishnan, B.; Adhikari, Prabha; Singh, Prakhar; Kabekkodu, Shama Prasada; Bhat, Samatha; Kadam, Anagha; Shetty, Avinash K
Abstract: Aim: The aim of this study was to examine the association between CD4 count, human papilloma virus (HPV) infection, and the risk of cervical intraepithelial neoplasia among HIV‐infected women. Methods: A cross‐sectional study was conducted among 104 HIV‐infected women attending an antiretroviral therapy clinic. They underwent Pap smear and cervical HPV DNA testing. Results: The overall prevalence of HPV infection was 57.7%. HPV 16 was the commonest genotype found (38.5%); HPV 16 and 18 put together contributed to 73.3% of HPV infection; 27.5% of HIV‐infected women had squamous cell abnormalities. Cervical intraepithelial neoplasia was less likely among women with CD4 count > 500/mm 3 (12%) and in those without opportunistic infections (17.8%). The prevalence of high‐risk HPV infection was higher in women with high‐grade squamous intraepithelial lesions or greater lesions (85.7%) as compared to women with normal cytology (52.1%). Conclusion: The high prevalence of HPV infection and cervical intraepithelial neoplasia in HIV‐infected women warrants the need for regular Pap smear screening in these women and routine HPV vaccination for adolescents to reduce the burden of cervical cancer in India.